Effect of Addition Tempeh Flour on Calcium, Protein, Water Content and Acceptance in Catfish Meatballs - Tammamia, Widyasmara Nur; Ningtyias, Farida Wahyu; Sulistiyani, Sulistiyani (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: More than 50% of women in each country suffer from dysmenorrhea.This can be painful during menstruation and affect 50% of a woman’s daily activities. Calcium can reduce muscle cramps after contractions. Tempeh and catfish are calcium-rich foods that people often eat, but the variety of processed products available is limited. The purpose of this study was to analyze the feasibility and compatibility of catfish meatballs with tempeh flour added with SNI fish meatballs as a healthy diet food for reducing dysmenorrhea in adolescents. Method: The research design applied was true experimental with 12 experimental units. The calcium content of the samples was determined using Atomic Absorption Spectrophotometry (AAS), the protein content used the Kjeldahl technique, the water content used the Oven method, and the acceptance test used the Hedonic Scale Test on adolescent. Data were analyzed using the One-Way ANOVA, and the acceptance test results were analyzed using the Friedman test with significance level α=0.05. The proportion of tempeh flour on catfish meatballs was 0% (P0), 10%, 20% and 30% (P10, P20, and P30). Results: The results showed that the adding tempeh flour could improve the levels of calcium, protein, and acceptability (taste) of catfish meatballs. The addition of 10 percent (P10) tempeh flour was an acceptable composition of the taste, but its value did not differ significantly from other recipes. Conclusion: Catfish meatballs P30 has the highest calcium and protein content. Further research is needed to fine-tune the flavor and confirm its effectiveness in reducing menstrual cramps.